2019
DOI: 10.5861/ijrsll.2019.4002
|View full text |Cite
|
Sign up to set email alerts
|

Training students to use online translators and dictionaries: The impact on second language writing scores

Abstract: Online translators have become an ever-present component of language learning. Recent research has found that online translators are used for graded work at least sometimes by 87.7% of intermediate students learning Spanish and French (O'Neill, 2019). The same percentage of students self-reports using online dictionaries. Given how widespread these tools are, the impact of their usage needs to be explored. Although some research has looked into the effects of online translation on writing, no previous study ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 17 publications
7
40
0
Order By: Relevance
“…Our findings suggest that translation gives multilingual students opportunities to leverage their linguistic repertoires in ways that their teachers may not otherwise be able to support, particularly in linguistically diverse classes, where the teacher cannot be expected to be proficient in all of the students’ languages (see also Cummins, 2007; Vogel et al., 2018). Given the limitations of translation tools that also became apparent in our study, we agree with previous studies that suggest teaching effective use of translation tools (Fredholm, 2019; O'Neill, 2019). However, we would add that such strategy instruction can build on students’ existing strategies (see also Vogel et al., 2018).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our findings suggest that translation gives multilingual students opportunities to leverage their linguistic repertoires in ways that their teachers may not otherwise be able to support, particularly in linguistically diverse classes, where the teacher cannot be expected to be proficient in all of the students’ languages (see also Cummins, 2007; Vogel et al., 2018). Given the limitations of translation tools that also became apparent in our study, we agree with previous studies that suggest teaching effective use of translation tools (Fredholm, 2019; O'Neill, 2019). However, we would add that such strategy instruction can build on students’ existing strategies (see also Vogel et al., 2018).…”
Section: Discussionsupporting
confidence: 92%
“…A translingual perspective also legitimizes translation by student writers on a more fundamental level. Even studies that have demonstrated positive effects of translation on writing in an additional language have questioned the value of translation tools if they do not eventually train language learners to produce the same results in the absence of the tools (Fredholm, 2019; O'Neill, 2019). Indeed, seen through a monolingual lens, translation has often been positioned as a stage to surpass on the way to near‐native mastery of the target language (Horner & Tetreault, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations